Pengaruh Tingkat Pendidikan Terhadap Partisipasi Politik Dalam Pemilihan Kepala Daerah Tahun 2020 Di Desa Serangan - Herlambang, Yuliana Santikawati; Riyanto, Agus (JURNAL LANSKAP POLITIK, 2022)
Aspects of education are able to make people have a broad view of the world of politics, the difference between people with high and low education can be seen from their attitudes and behavior. This study aims to determine the effect of education level on community political participation in the 2020 regional head election in Serangan Village. The method used in this research is a quantitative research method. The data analysis technique used is the research instrument test, classical assumption test, simple linear regression analysis, correlation coefficient test, t hypothesis test, and coefficient of determination test. Based on the results of the research and discussion carried out, it can be concluded that the level of education has a positive and significant relationship with community political participation, for the category of relationship is classified in a weak relationship with a magnitude of 6.5%. For 93.5% influenced by other variables not examined by the researcher.